2020
DOI: 10.1016/j.jcot.2019.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Cement-in-cement revision with the Exeter Short Revision Stem: A review of 50 consecutive hips

Abstract: Revision of a well-fixed cemented femoral stem is technically challenging. The Exeter Short Revision Stem (SRS) was developed to facilitate cement-in-cement revision mitigating some of these challenges. We present the short to mid-term results of 50 cement-in-cement revisions performed with this implant.A retrospective review of all cement-in-cement revision with the Exeter SRS, at our institution, over a seven-year period between 2007 and 2014 was conducted. Records were assessed for radiological and clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“… 2 , 8 , 17 Within the V40 range, multiple predisposing factors have been proposed, associated with both surgical factors (notch sensitivity, increased offset and femoral head size, propagation from the insertion hole, 2 , 5 , 13 , 18 , 19 ) and patient factors (higher activity level and raised BMI). 15 , 19 , 24 In our study, neck fractures were associated with standard-length stems (83%) and raised BMI (83%). Previous metallurgical studies of Exeter stem neck fractures demonstrate ductile deformation highly indicative of a high-cycle low-stress fatigue failure.…”
Section: Mechanism Of Fracturementioning
confidence: 50%
See 1 more Smart Citation
“… 2 , 8 , 17 Within the V40 range, multiple predisposing factors have been proposed, associated with both surgical factors (notch sensitivity, increased offset and femoral head size, propagation from the insertion hole, 2 , 5 , 13 , 18 , 19 ) and patient factors (higher activity level and raised BMI). 15 , 19 , 24 In our study, neck fractures were associated with standard-length stems (83%) and raised BMI (83%). Previous metallurgical studies of Exeter stem neck fractures demonstrate ductile deformation highly indicative of a high-cycle low-stress fatigue failure.…”
Section: Mechanism Of Fracturementioning
confidence: 50%
“… 27 , 28 More recently, multiple studies in Asia and the UK demonstrated survival rates of 100% for aseptic loosening for the Exeter Universal 35.5 mm shorter stems at ten and eight years, respectively. 27 , 29 The success of the V40 Exeter short revision stem (44/00/125) introduced in 2005 is well published in providing an implant which facilitates restoration of leg length, offset and stability, while limiting bone loss secondary to excess reaming in revision 22 , 24 , 30 and recently primary THA. 30 …”
Section: Discussionmentioning
confidence: 99%
“…Berg et al. [ 8 ] presented a case series of 50 short Exeter stems (44/00/125) used in c-in-c revisions, none of which were performed for periprosthetic fracture, and had 1 stem fracture (2%) in their cohort. Woodbridge et al.…”
Section: Discussionmentioning
confidence: 99%
“…The c-in-c technique has been well described for its use in revision arthroplasty in other settings [ [8] , [9] , [10] , [11] , [12] ], but little has been described regarding its use in periprosthetic fractures. Woodbridge et al.…”
Section: Introductionmentioning
confidence: 99%
“…Quinlan et al had an excellent outcome using the cement-in-cement technique [22]. Other studies also showed results with the new technique and a decrease in complications due to the revision [5,13,23,24]. Sandiford et al also investigated the cement-in-cement technique in multiple revised total hip replacements.…”
Section: Discussionmentioning
confidence: 99%